2016
DOI: 10.15171/ijhpm.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived Mental Health Status and Uptake of Fecal Occult Blood Test for Colorectal Cancer Screening in Canada: A Cross-Sectional Study

Abstract: Background: While colorectal cancer (CRC) is one of the most preventable causes of cancer mortality, it is one of the leading causes of cancer death in Canada where CRC screening uptake is suboptimal. Given the increased rate of mortality and morbidity among mental health patients, their condition could be a potential barrier to CRC screening due to greater difficulties in adhering to behaviours related to long-term health goals. Using a population-based study among Canadians, we hypothesize that self-perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The improvement in the level of knowledge as a result of health education received may increase the uptake of PHS in order to prevent likely comorbidities. 11,[22][23][24][25][26] This is similar to the study conducted among Korean workers which showed that having at least one chronic disease was associated with a higher uptake of preventive health services. 10 There was no significant association between religion and uptake of PHS.…”
Section: Discussionsupporting
confidence: 71%
“…The improvement in the level of knowledge as a result of health education received may increase the uptake of PHS in order to prevent likely comorbidities. 11,[22][23][24][25][26] This is similar to the study conducted among Korean workers which showed that having at least one chronic disease was associated with a higher uptake of preventive health services. 10 There was no significant association between religion and uptake of PHS.…”
Section: Discussionsupporting
confidence: 71%
“…We will also conduct subanalyses using data from CCHS 1.2 Cycle and CCHS 2012 for Mental Health, which contain validated measures for mood and anxiety disorders 34. Symptoms will be based on the following questions that have been used in previous studies45 59–64:…”
Section: Methods and Analysismentioning
confidence: 99%
“…Several studies have reported that individuals experiencing psychological distress (PD), such as depression or anxiety, are less likely to participate in cancer screening. According to our in-house, preliminary, systematic review, most population-based studies examining the associations between PD and screening for colorectal, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] breast, 1-6,10,14-21 or cervical cancers 1,3,10,15,[17][18][19][22][23][24] have been conducted in North America or Europe. One meta-analysis reported a significant reduction in mammography screening rates among women with mood disorders.…”
Section: Introductionmentioning
confidence: 99%